Factors Influencing the Choice of Higher Education Establishment for Marketing Strategies of Higher Education - Sarkane Glorija; Sloka Biruta (Economics and Business)
The world-wide competition of higher education programs makes education institutions to seek for most efficient ways to attract students. The presented academic research is devoted also to the issues on motives and influencing factors for the choice of study programs. The methods applied in the current paper are as follows: analysis of scientific publications, focus group discussions, surveys of possible future students. For the evaluation of different aspects of choice a scale of 1-10 was used. For the data analysis of the survey descriptive statistical analysis, cross tabulations and correlation analysis, as well as analysis of variance (ANOVA) and factor analysis were applied.